Music and Theology in Erik Peterson’s Writings - García-Plaza, Amparo (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
This article analyzes excerpts of Erik Peterson’s work where music is related to theology, usually in connection with the communitarian singing in God’s praise that takes place during liturgy. The Petersonian reflection about this subject is presented following the scheme of the various dimensions of liturgical singing highlighted by this author: cosmic, eschatological, public-political, ecclesial communitarian and existential-spiritual dimensions.
Keywords: Erik Peterson; music; singing; eschatology; liturgy; God’s praise; acclamation; monasticism; angels